Research on Bond Participants’ Emotion Reactions Toward the Internet News in China’s Bond Market - Zhang, Wei; Wang, Jun; Tong, Mu (Frontiers in Psychology, 2022)
This paper applies a range of regressions to examine the emotion reactions of credit rating agencies (CRAs) and bond investors to the financial news from the internet between 2010 and 2020 in China. The main findings are as follows: (1) CRAs are inclined to ignore the warnings of financial news on the internet, whereas bond issuers with more bad news are more likely to seek credit guarantees to enhance credit ratings; (2) both bad news and good news have an impact on the bond investors in general, but bond investors has a stronger response to the bad news; (3) considering the firm ownership, the news relating to central state-owned firms has no impact on the bond investors; (4) with regards of the news timeliness, both the latest news and old news affect bond investors, but investor emotions are more sensitive to the latest news. Overall, this study has significance for bond investors and regulators to assess the risk associated with financial news.